STRUKTUR DAN KOMPOSISI VEGETASI PADA KAWASAN LINDUNG AIR TERJUN TELAGA KAMELOH KABUPATEN GUNUNG MAS - Nicko Haryadi (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2017)
Diversity is a natural characteristic and is the basis of ecological stability, biodiversity expressed a measure that describes the variation of plant species from a community that is affected by the number of species and relative abundance of each species. The presence of trees at a site generally will have a positive impact for the balance of the ecosystem in a wider scale. In general, the role of vegetation in an ecosystem associated with the regulation of carbon dioxide and oxygen balance in the air, improved physical properties, chemical and biological soil, ground water system settings, and others. The behavior of each type of tree growth and regeneration of species adaptation to environmental changes are a result of degradation is very useful information for consideration in determining the form of further processing of forest. The purpose of this study was to determine the structure and composition of vegetation in the protected area forest Telaga Kameloh waterfall area in subdistrict Kurun district Gunung Mas. Note that the value of diversity type (H ') from all levels of vegetation; seedling, stake, poles and trees, the largest located in protected areas with high diversity (H> 3 - 3,5). Richness of Species with the highest seedling of protected areas with a value of 7,49 in areas with the highest degradation of seedlings is 5.27. The highest value of evenness of species found on poles level in areas hedge with the value 0.97 and the area of degradation value with the highest poles evenness of 0.96. Dominance index (C) the highest found in tree in protected area 16,73, in the area of degradation value of the highest dominance on the tree with the value 23,37. Community similarity index or index of similarity (IS) has a value Of between 44,53% to 77.07%.The vegetation structure in degradasi area from curve J is inversed, it sign that the comumity was annoyed. In the protected area, vegetation structure not from curve J inversed.